The Effects of Altitude Training on Erythropoietic Response and Hematological Variables in Adult Athletes: A Narrative Review - Płoszczyca, Kamila; Langfort, Józef; Czuba, Miłosz (Frontiers in Physiology, 2018)
Background: One of the goals of altitude training is to increase blood oxygen-carrying capacity in order to improve sea-level endurance performance in athletes. The elevated erythropoietin (EPO) production in hypoxia is a key factor in the achievement of enhanced hematological variables. The level of the EPO increase and acceleration of erythropoiesis depend on the duration of exposure and degree of hypoxia. Furthermore, many other factors may affect the hematological response to altitude training. Aim: The purpose of this narrative review was to: (1) analyze the kinetics of EPO and hematological variables during and after altitude training; (2) summarize the current state of knowledge about the possible causes of individual or cohort differences in EPO and hematological response to altitude training; (3) formulate practical guidelines for athletes to improve the efficiency of altitude training. Methods: A narrative review was performed following an electronic search of the databases PubMed/MEDLINE and SPORTDiscus via EBSCO for all English-language articles published between 1997 and 2017. Results: Complete unification of results from studies on EPO kinetics was difficult due to different time and frequency of blood sampling by different researchers during and after altitude training, but the data presented in the reviewed literature allowed us to detect certain trends. The results of the reviewed studies were divergent and indicated either increase or no change of hematological variables following altitude training. Factors that may affect the hematological response to altitude training include hypoxic dose, training content, training background of athletes and/or individual variability of EPO production. Conclusions: Despite the potential benefits arising from altitude training, its effectiveness in improving hematological variables is still debatable. Further research and better understanding of factors influencing the response to altitude, as well as factors affecting the suitable measurement and interpretation of study results, are needed.